2000
DOI: 10.1007/s101570070030
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features of antineutrophil cytoplasmic antibodies-associated vasculitis in Japanese patients with IgA nephropathy

Abstract: Antineutrophil cytoplasmic antibodies (ANCA) have been reported to be associated with systemic vasculitis. However, the roles of ANCA subtypes in patients with IgA nephropathy remain to be fully investigated. We describe three Japanese patients with IgA nephropathy complicated by ANCA-associated vasculitis. Two patients with IgG class ANCA developed rapidly progressive renal failure and demonstrated mesangial proliferation with extensive extracapillary proliferation and segmental glomerular necrosis. One patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…However, whether immune complex containing IgA could lead to production of ANCA remains debated. Elevation of serum tumour necrosis factor-α, soluble forms of intercellular adhesion molecule 1 and urinary interleukin-8 levels could be detected in the acute or deteriorating phase of IgAN [ 22 24 ], which could possibly result in the activation of polyclonal B cells and in the formation of ANCA [ 15 ]. However, we found that IgAN patients with ANCA positivity were relatively older than ANCA-negative patients, and the presence of ANCA was rarely seen even in the acute or deteriorating phase of IgAN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, whether immune complex containing IgA could lead to production of ANCA remains debated. Elevation of serum tumour necrosis factor-α, soluble forms of intercellular adhesion molecule 1 and urinary interleukin-8 levels could be detected in the acute or deteriorating phase of IgAN [ 22 24 ], which could possibly result in the activation of polyclonal B cells and in the formation of ANCA [ 15 ]. However, we found that IgAN patients with ANCA positivity were relatively older than ANCA-negative patients, and the presence of ANCA was rarely seen even in the acute or deteriorating phase of IgAN.…”
Section: Discussionmentioning
confidence: 99%
“…No more than 30 cases with IgAN and coexisting IgG-ANCA positivity have been reported to date, mainly case reports [ 1 – 15 ] and two case series [ 16 , 17 ]. O'Donoghue found that 2% of patients with IgAN showed serum IgG-ANCA positivity.…”
Section: Introductionmentioning
confidence: 99%
“…A case of an adult renal allograft recipient with recurrent IgA nephropathy has been reported, where IgA-ANCA but not IgG-ANCA, was increased after renal transplantation, suggesting that IgA-ANCA might be associated with disease activity. 4 Shimizu et al 5 suggest that the detection of IgM-ANCA in IgA nephropathy may have a close relationship with the extrarenal symptoms of systemic vasculitis, as well as the renal involvement. In previous reports, most cases of IgG-ANCA (MPO-ANCA)-positive IgA nephropathy seem to have been severe, with crescent formation in glomeruli and elevated serum creatinine levels having been observed (Table 3).…”
Section: Discussionmentioning
confidence: 98%
“…14 Upregulation of these cytokines and adhesion molecules may induce polyclonal B-cell activation and amplify ANCA production, leading to crescent formation with necrotizing vasculitis. 5 It was reported that serum TNF-α, ICAM-1, and urinary IL-8 were elevated in patients with acute onset or exacerbation of IgA nephropathy. 15,16 When tonsillitis occurs, patients with IgA nephropathy often develop hematuria and acute lesions such as cellular crescent formation and blood capillary necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the kidney involved by AAV is often characterized by pauci-immune glomerulonephritis, but there is increasing evidence that immune complex deposition can coexist with ANCA-associated glomerulonephritis. Some studies suggested that immune complexes might appear in the early stage of vasculitis and take part in the occurrence of ANCA and the activation of inflammatory reaction, and then initiated to activation of polyclonal B cells and formation of ANCA [3, 31]. In time, the existence of ANCA would aggravate the inflammatory reaction and lead to pauci-immune injury.…”
Section: Discussionmentioning
confidence: 99%